Kampanye Solidaritas Melalui E-Pamflet All Eyes on Rafah Perspektif Mark Slouka - Zuhdi, Moh. (Universitas Brawijaya, 2025)
This study aims to explore the e-pamphlet All Eyes on Rafah as a solidarity campaign. The All Eyes on Rafah campaign emerged in response to the humanitarian crisis in Rafah, using e-pamphlets as a primary means to raise global attention and solidarity towards the suffering of Gaza's residents. The method used is qualitative and interpretive. This research examines how messages of solidarity are disseminated, functioning as a tool for social mobilization. The theory used for interpretation refers to the concept proposed by Mark Slouka regarding the digital public sphere and the role of media in shaping social awareness. The findings show that e-pamphlets play a crucial role in mobilizing international support, although they also reveal limitations in achieving long-term structural change.